وسائل الإدارة القانونية لإزالة التجاوز على الأموال العامة - المهشم، سامى خلف; إسماعيل، محمد سعيد أحمد (جامعة البعث, 2018)
The modern state has been carrying out many tasks and duties that are increasing day by day, especially after the retreat of individual doctrine and State intervention in various fields. In order for the state to carry out its functions as defined in the Constitution and laws, it must have the means and tools to enable it to carry out its tasks in the fullest these instruments and tools are embodied in a range of public funds, whether movable or immovable, which are necessary and important to ensure the continued functioning of public utilities. These funds may be subjected to various forms of abuses by individuals, which require the state to intervene through its devices in order to raise this abuse through a number of ways and means that the law has placed at the disposal of the administration under certain controls. Therefore, in order to raise the excess of its property, the Department is able to make administrative decisions to compel individuals to raise abuse; it removes this abuse through the courts in the form of civil suits and criminal proceedings, which we will address in our search.
الدولة الحديثة أصبحت تقوم بالعديد من المهام والواجبات والتي تتزايد يوما بعد يوم وخصوصا بعد تراجع المذهب الفردي وتدخل الدولة في شتى المجالات. ولكي تقوم الدولة بمهامها المحددة في الدستور والقوانين لابد أن يتوفر لها الوسائل والأدوات التي تمكنها من أداء مهامها على أكمل وجه وقد تتجسد هذه الوسائل والأدوات بمجموعة من الأموال العامة سواء كانت منقولة أو عقارية وهي أموال ضرورية وهامة لضمان دوام سير عمل المرافق العامة وقد تتعرض هذه الأموال لمختلف أشكال الاعتداء والتجاوزات التي تقع من قبل الأفراد مما يتطلب تدخل الدولة عبر أجهزتها لرفع هذا التجاوز وذلك من خلال عدة طرق ووسائل وضعها القانون تحت تصرف الإدارة ضمن ضوابط معينة. وعلى ذلك تستطيع الإدارة وفي سبيل رفع التجاوز الواقع على ما تملكه من أموال أن تلجأ إلى إصدار القرارات الإدارية لإلزام الأفراد برفع هذا الاعتداء وكما تلجأ أيضا لرفع هذا التجاوز عن طريق القضاء وذلك على شكل دعاوى مدنية ودعاوى جزائية وهذا ما سنتناوله في بحثنا.
Keywords: القوانين والتشريعات -- الإدارة القانونية -- القرارات الادارية -- الأموال العامة